2020
DOI: 10.1002/maco.202011674
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and corrosion behavior of FeCrNiMnMox high‐entropy alloys fabricated by the laser surface remelting

Abstract: In this study, an Nd:YAG laser was used to carry out laser surface remelting treatment on FeCrNiMnMo x (x = 0, 0.5, 1) alloys. A study was conducted on the potential impact of Mo on the microstructure and corrosion resistance of the laser-remelted layer. According to the research results, FeCrNiMnMo x alloys were more effective in refining the dendrites, compared with the matrix, whereas the FeCrNiMn alloys' remelted layer exhibited an almost single face-centered cubic (FCC) structure. In comparison, FeCrNiMnM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Due to the laser quenching effect of laser surface remelting treatment and the precipitation of nanoscale particulate matter after aging, heat treatment enhanced the hardness and wear resistance of the alloy, but they did not investigate the surface corrosion resistance of the material, which is very important as it relates to the environment in which the material is applied. Hu et al [12] examined the corrosion resistance of remelted layers by laser surface remelting of FeCrNiMnMo x (x = 0, 0.5, 1) alloys using a Nd:YAG laser. The results showed that the dendritic structure of the remelted alloy was significantly refined compared with the matrix due to the combined effect of Mo alloying and rapid solidification of the remelted surface, and the addition of Mo accelerated the formation of Cr 2 O 3 , improved the stability of the passivation film, and significantly improved the corrosion resistance in a 3.5% NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the laser quenching effect of laser surface remelting treatment and the precipitation of nanoscale particulate matter after aging, heat treatment enhanced the hardness and wear resistance of the alloy, but they did not investigate the surface corrosion resistance of the material, which is very important as it relates to the environment in which the material is applied. Hu et al [12] examined the corrosion resistance of remelted layers by laser surface remelting of FeCrNiMnMo x (x = 0, 0.5, 1) alloys using a Nd:YAG laser. The results showed that the dendritic structure of the remelted alloy was significantly refined compared with the matrix due to the combined effect of Mo alloying and rapid solidification of the remelted surface, and the addition of Mo accelerated the formation of Cr 2 O 3 , improved the stability of the passivation film, and significantly improved the corrosion resistance in a 3.5% NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…For the factors dominating the corrosion resistance of alloys, except for the internal factors of composition and microstructure, [ 17–29 ] some external impacts are also essential to be considered. It is generally accepted that the temperature, electrolyte, and surface roughness are the most common factors affecting the actual corrosion performance of metallic materials.…”
Section: Introductionmentioning
confidence: 99%